Water Pollution Index in the Ekas Bay Floating Net Cage Area as Part of Sustainable Aquaculture - Diniarti, Nanda; Junaidi, Mohammad; Setyono, Bagus Dwi; Asri, Yuliana; Dwiyanti , Septiana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Fish cultivation using the Floating Net Cultivation (FNC) system had the potential to create nutrient enrichment around the cultivation location. The large amount of nutrient input in marine waters can cause algae blooms also known as eutrophication. If this condition continues to occur, biota diversity will decrease and cause the seas to lose their function, so before that happens, it is considered to periodically monitor the pollution index in the Ekas Bay FNC area. The aim of this study is to analyze the pollution index in FNC area in the waters of Ekas Buana Village. The value obtained can be used as a basis for managing the area to create sustainable and sustainable use. The research was conducted in Ekas Bay, Ekas Buana village, East Lombok district on June-September 2023. The parameters observed were physical and chemical water quality parameters. The data that has been collected will be analyzed descriptively and presented in the form of tables and graphs. The parameter value obtained was the only one that passed the quality standard based on PP No. 22 of 2021, namely orthophosphate. Phosphate is indeed abundant in marine waters, but it will cause blooming if the total supply of ammonia nitrogen is excessive. From the pollution index, it was found that the East station, which is the coastal littoral area, is classified as moderately polluted, while the other stations are classified as lightly polluted. The sources and quantities of the pollution need to be identified to facilitate control and prevent further pollution.